PENGARUH KUALITAS GURU TERHADAP KEMAMPUAN GURU DALAM MEMVARIASIKAN PEMBELAJARAN - Muhammad Darwis, Dasopang (Institut Agama Islam Negeri Padangsidimpuan, 2017)
Good or bad of a learning process is influenced by several factors, one of which is the quality of the teacher in teaching. This study aims to analyze the effect of teacher quality on the ability of teachers to vary learning. This research is a quantitative study with an experimental research approach. The sample of this study were Islamic Religious Education teachers. The sampling technique used is cluster random sampling. This study uses a questionnaire and observation sheet as data collection techniques. Data analysis techniques in this study are descriptive and inferential statistics. The results showed that there was a significant influence between the quality of teachers on the ability to vary learning with a significance level 0.005. The better the quality of the teacher, the better his ability to provide variations in teaching